Effect of dirty-hold time on cleaning process of pharmaceutical equipment - Patera, Jan; Stípková, Gabriela; Zámostný, Petr; Bělohlav, Zdeněk; Vltavský, Zdeněk (Pharmaceutical development and technology, 2013)
The work was aimed at the evaluation of a cleanliness of pharmaceutical equipments after the end of the production and subsequent cleaning process. The influence of a dirty-hold time, a time interval between the end of the production period and the beginning of the cleaning process on its efficiency and the cleanliness of the equipment has been studied. The evaluation was performed for commercial tablet antihypertensive formulation with API losartan potassium. Sampling was carried out by a wet-swabbing method from the equipments and consequently obtained samples were analytically evaluated using HPLC. In the production of the concerned pharmaceutical, it has been found that the cleaning process is properly designed and validated. Despite the concentration of losartan in swabs from the equipment was in all cases within the limits of acceptance criteria, the effect of the dirty-hold time was proved. In the equipments with long hold-time period, the monitored substance was found in substantially higher concentrations.
Keywords: vysokoúčinná kapalinová chromatografie; příprava léků; časové faktory; Equipment Contamination; Time Factors; farmaceutický průmysl; Antihypertensive Agents; Chromatography, High Pressure Liquid; Drug Compounding; Drug Industry; antihypertenziva; losartan; Tablets; tablety; Losartan; kontaminace zdravotnického vybavení